Comparative Evaluation of Mechanical, Structural, and Morphological Properties of Corncob Ash and Graphite-Filled Epoxy Composites - Oluwaseyi Omotayo Taiwo; Darlington Chinaza Amadi; Binah Somtochukwu Ojiyi; Nmesoma Godswill Ofomata; Blessed Obinna Mayor; Oluwasegun Biodun Owolabi (SciencePlus, 2026)
This study presents a comparative investigation of the mechanical, structural, and morphological properties of epoxy composites reinforced with corncob ash (CCA) and graphite fillers at varying weight percentages (0–25 wt%). Composite specimens were fabricated using the hand lay-up technique and characterised through tensile, flexural, impact, and hardness tests, complemented by X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray (EDX) analyses. The results revealed that corncob ash epoxy composites exhibited a maximum tensile strength of 14.34 MPa at 25 wt% filler loading, while graphite epoxy composites achieved the highest tensile strength of 13.24 MPa at 5 wt% loading. The highest Vickers hardness values were 25 HV and 22.37 HV for CCA and graphite composites at 25 wt%, respectively. Graphite composites demonstrated superior impact strength (5.44 J at 25 wt%), while CCA composites showed comparable performance (5.17 J at 0 wt% control). Flexural strength peaked at 15 wt% for both fillers, with graphite composites reaching 38.77 MPa and CCA composites achieving 32.24 MPa. XRD analysis confirmed crystalline phases in both composite systems, and SEM/EDX characterisation revealed the dispersion behaviour and elemental composition of the fillers within the epoxy matrix. The findings suggest that corncob ash, an agricultural waste material, is a viable and sustainable alternative to conventional graphite filler in epoxy composite applications, offering comparable mechanical performance with significant environmental and economic advantages